Analisis Kritis Studi Literatur Tentang Dampak Perubahan Iklim Terhadap Ketahanan Pangan - Suarja, Zul Erianto; Triwandoyo, Denny; Zebua, Vestin; Tafonao, Siska Ayu Lestari (Jurnal Ilmu Pertanian dan Perikanan, 2024)
Climate change impacts global food security through reduced crop yields, disruptions in supply chains, decreased food quality, and pressure on water availability. This study reviews the literature on the effects of climate change on food security and finds that rising temperatures, changing precipitation patterns, and extreme weather events significantly affect food production, distribution, and accessibility. Crop yield reductions are attributed to higher temperatures shortening the growing period of plants, while climate change also affects the nutritional quality of crops and exacerbates water crises. Disruptions in supply chains lead to increased food prices, disproportionately affecting vulnerable groups. Proposed adaptation strategies include developing climate-resilient crop varieties, improving water use efficiency, and implementing sustainable agricultural practices, alongside developing supportive policies for food security